Analisis Efektivitas Penyaluran Zakat Produktif Dalam Meningkatkan Pendapatan Mustahik (Studi Kasus BAZNAS Kota Yogyakarta) - arista, zuli arista (Jurnal Rekoginisi Ekonomi Islam, 2025)
This study examines the analysis of the effectiveness of productive zakat distribution in increasing mustahik income at BAZNAS Yogyakarta City. This study uses a qualitative approach with a descriptive method, data is collected through field research with observation techniques, interviews and document analysis with coding data analysis techniques. The results of this study indicate that the distribution of zakat to increase business income at BAZNAS Yogyakarta City has proven to be effective. To measure its effectiveness, it is seen from the accuracy of the target that has been proven to have distributed assistance to the poor who need business capital assistance, socialization has been proven to have carried out socialization to the community before the program was implemented, the objectives have been proven to have been achieved according to plan, and monitoring has been proven to have been monitored every month. The productive zakat distribution program that is run has had a positive impact on recipients of business capital assistance, proven to increase the income of business actors (mustahik). This assistance has had a significant impact on improving the standard of living, especially for those experiencing economic difficulties.